Nurses' interventions in preventing pressure injury in an intensive therapy unit - Rigielli Ribeiro Manganelli; Raquel Soares Kirchhof; Greice Machado Pieszak; Carla da Silveira Dornelles (Universidade Federal de Santa Maria, 2019)
Aim: to characterize the studied population and to describe the interventions of the nurses for the prevention of pressure injury in an Adult Intensive Care Unit. Method: descriptive, cross-sectional study with 13 nurses from an Intensive Care Unit, carried out between August and September 2017. A questionnaire and descriptive statistics were used. Results: female participants predominated (84.9%) and the mean age was 29.9 years of age. In order to prevent pressure injury, evidence-based care, scientific basis and institutional protocols were evidenced. The most frequently mentioned care included assessment of patients' mobility and physical examination at admission. As preventive care, the nurses prescribed the maintenance of the patient with hydrated skin, alternating decubitus, body hygiene and the use of pyramidal mattress. Conclusion: nurses use significant interventions in the prevention of pressure injury, but there are still gaps in care provided.